Relação entre insuficiência/deficiência da vitamina d, inflamação e estresse oxidativo em adolescentes escolares com excesso de peso - Queiroz, Dayanna Joyce Marques (2016)
INTRODUCTION: Adolescence comprises the age 10-19 years. This phase is marked biological and physiological changes, including highlighting the bone mineral growth, which is dependent on the nutritional status of calcium and vitamin D. In recent years, studies of adolescents showed high rates of failure / vitamin D deficiency in several countries. Vitamin D has an important role in bone growth and recent evidence has associated the vitamin D status with diabetes, hypertension, cancer and increased biomarkers of oxidative stress and inflammation in adults and the elderly. In adolescents, studies have shown an association between low serum concentrations of vitamin D and the increase in cardiometabolic risk factors. OBJECTIVE: The aim of this study was to evaluate the insufficiency/deficiency of vitamin D and its association with cardio metabolic risk factors in adolescents. METHODS: A Cross-sectional study including 209 adolescents aged 15 to 19 years old, recruited from public schools in the city of João Pessoa, Brazil. Personal data and sun exposure were collected through questionnaires. The dietary intake was assessed by applying a 24-hours recall. Nutritional status was assessed by body mass index (BMI), waist circumference (WC) and the waist-to-height ratio (WHtR) according to the cut-offs for age criteria. Blood pressure was measured according to the protocol of the Brazilian Society of Hypertension. It was collected blood samples to measure levels of 25-hidrovitmina D, Parathyroid hormone, glucose and lipid profile, C-reactive-protein (CPR), alpha-1-acid-glycoprotein(AGP-A), malondialdehyde (MDA), and total antioxidant capacity (TAC). The research was approved by the Research Ethics Committee of the CCS / UFPB under the Protocol 0139/15. Statistical analysis was performed using the "Statistical Pac age for Social Sciences" (SPSS Inc., Chicago, USA), version 21, adopting significance of p <0.05. RESULTS: The insufficiency/deficiency (≤ 30 ng/mL) of vitamin D was observed in 57, 4 % (CI 95% -50,6-64) of the adolescents, and in 76 % (CI 95%-62,8-86,3) of those were overweight. Dietary intake of vitamin D was inadequate ( 60 ± 18 μg) in 100% of the sample. Low levels of 25 (OH) D were associated with female gender (RP= 2, 3; CI 95% = 1, 8-3, 5; p=0), central adiposity measures by the WC (p = 0.02) and WHR (0.01), lower TAC (p = 0.01) and serum calcium (p = 0.00). The adolescents showed an inverse correlation between the total cholesterol (p = 0.01; r = -0.167) and BMI (p = 0.02; r = -0.166) with the levels of 25 (OH) D. The CPR values, the AGP-A, and MDA were increased in those that were both vitamin D deficient/insufficient and overweight (p = 0.00). CONCLUSION: The insufficiency/deficiency of vitamin D was associated with BMI, WC and WHtR, lower TAC and higher total cholesterol levels, suggesting that inadequate levels of vitamin D promotes the increased risk in the development of diseases associated with overweight, process inflammatory and oxidative stress.